PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN INDIHOME DI BOGOR - Djodi Pangestu, (2021)
The purpose of this study is to analyze and prove the effect of product quality and service quality on Indihome consumer satisfaction. The type of data used is quantitative data. The population used is Indihome consumers in Bogor. The number of samples used is 100, namely consumers who have or are currently using Indihome products with purposive sampling method. This study uses data analysis techniques, namely inferential analysis and Partial Least Square (PLS) analysis with analysis tools using SmartPLS software. 3.3.3. The results obtained from this study are that the product quality variable has an effect on consumer satisfaction and the service quality variable has an effect on consumer satisfaction.